Genetic diversity reflects geographical origin of Ralstonia solanacearum strains isolated from plant and water sources in Spain - Caruso, Paola; Biosca, Elena G.; Bertolini, Edson; Marco-Noales, Ester; Gorris, María T.; Licciardello, Concetta; López, María M. (Sociedad Española de Microbiología, 2020)
The characterization and intraspecific diversity of a collection of 45 Ralstonia solanacearum strains isolated in Spain from different sources and geographical origins is reported. To test the influence of the site and the host on strain diversity, phenotypic and genotypic analysis were performed by a polyphasic approach. Biochemical and metabolic profiles were compared. Serological relationship was evaluated by Indirect-ELISA using polyclonal and monoclonal antibodies. For genotypic analysis, hrpB and egl DNA sequence analysis, repetitive sequences (rep-PCR), amplified fragment length polymorphism (AFLP) profiles and macrorestriction with XbaI followed by pulsed field gel electrophoresis (PFGE) were performed. The biochemical and metabolic characterization, serological tests, rep-PCR typing and phylogenetic analysis showed that all analysed strains belonged to phylotype II sequevar 1 and shared homogeneous profiles. However, interesting differences among strains were found by AFLP and macrorestriction with XbaI followed by PFGE techniques, some profiles being related to the geographical origin of the strains. Diversity results obtained offer new insights into the biogeography of this quarantine organism and its possible sources and reservoirs in Spain and Mediterranean countries.